Enriching English in School Education: Some Problems and Principles - Poudel, Ambika Prasad (Rupantaran: A Multidisciplinary Journal, 2020)
English is a widely used language in international communication. It is a storehouse of knowledge that most of the books, and journal articles have been published in English, and it is the dominant language in the Internet. Realizing this fact, the government of Nepal has made English one of the core components of school education curricula. However, teaching and learning of English in the schools in Nepal has been influenced by several problems. Using systematic literature review as the methods, this article makes an attempt to highlight the major problems that exist in teaching and learning of English in school education in Nepal, and points out some principles for enriching English in the learners. This study has been expected to add at least some insights to those who are interested in enhancing English education in Nepal.